Inovasi Bisnis “Toko Barokah” Melalui Service Dan Customer Engagement Untuk Meningkatkan Keuntungan - Nurus Sa’adah; Beni Dwi Komara (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The number of modern retail businesses has an unfavorable impact on traditional retail businesses. The high level of competition in the business world makes traditional retail store entrepreneurs have to be wise in determining strategies so that their business can survive and be able to develop. Moreover, the covid19 pandemic, entrepreneurs are demanded to be more innovative because there have been so many changes in customer behavior and the decline in the middle-level market has turned into a lower economy. The purpose of this study is to find out the retail store business model, the impact of the covid-19 pandemic on retail stores and find out the innovations made by the Cahaya Putra store. Based on the results of research in the field and the business model of the Cahaya Putra store, the costumer segment of the Cahaya Putra store is factory workers, project workers. Value Propositions provide products that consumers need. The impact of the Covid-19 pandemic was also felt by the Cahaya Putra store, the existence of PPKM which made retail stores close faster which made the store's revenue decrease because they took a little profit so that customers did not switch to competitors. Toko Cahaya Putra innovates to maintain and improve its business through the implementation of Customer Engagement Innovation with tactical Personalization and Guarantee.